POWERED APPLICATIONS ARCHIVING PROGRAM IRRIGATION - Ria Subasita; Yulina Yulina, SKom, MMSI (Jurnal Sistem Informasi, 2009)
Many government agencies are still using manual systems developments in processing data when the computer is becoming more sophisticated, so can help the processing of data. Management still using the system manually, often cause problems such as information becomes ineffective and efficient, and hard search on the data when needed. This is what happens on one of the Institute of Irrigation government agencies during the processing of archived data. In this context, the authors are interested in creating a system Computerized archiving. In this study discusses the process archiving system, Data Flow Diagrams (DFD), Entity Relationship Diagram (ERD), Normalization and programs using Microsoft Visual Basic 6.0.